2015
DOI: 10.2308/ciia-51279
|View full text |Cite
|
Sign up to set email alerts
|

How Client Identification and Client Commitment Uniquely Influence Auditor Objectivity

Abstract: SUMMARY This article summarizes our recent study, “Client Identification and Client Commitment in a Privately Held Client Setting: Unique Constructs with Opposite Effects on Auditor Objectivity” (Herda and Lavelle 2015), which examines how individual auditors' identification with, and commitment to, privately held audit clients affects their objectivity. Based on a survey of 102 external auditors, we find that client identification is distinct from client commitment. This distinction is importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Harda and Lavelle (2015) indicate that identifying with the owner impairs the auditor's neutrality. Sweeney and Pierce (2006) showed that transformational leadership could have a negative impact on auditor neutrality.…”
Section: Theoretical Framework and Backgroundmentioning
confidence: 99%
“…Harda and Lavelle (2015) indicate that identifying with the owner impairs the auditor's neutrality. Sweeney and Pierce (2006) showed that transformational leadership could have a negative impact on auditor neutrality.…”
Section: Theoretical Framework and Backgroundmentioning
confidence: 99%
“…The third theory related to employee engagement is social exchange theory, which concerns the relationship between the organization and employee (Gilliam & Rayburn, 2016 Another study conducted by Herda and Lavelle (2015) and related to the social exchange theory, examined the relationship between 102 auditors from a large private audit firm in the United States, and their clients. The conclusion was that clients preferred social exchanges rather than transactional exchanges (Herda & Lavelle, 2015). The relationship between auditor and client, and the way the auditor viewed the social exchange relationship will determine the auditor's level of engagement (Herda & Lavelle, 2015).…”
Section: Alternative Theoriesmentioning
confidence: 99%
“…The conclusion was that clients preferred social exchanges rather than transactional exchanges (Herda & Lavelle, 2015). The relationship between auditor and client, and the way the auditor viewed the social exchange relationship will determine the auditor's level of engagement (Herda & Lavelle, 2015). Leaders who build strong relationships with subordinates or clients are more effective at increasing employee engagement because people are more willing to follow leaders with whom they have a relationship (Hamon & Bull, 2016).…”
Section: Alternative Theoriesmentioning
confidence: 99%